Development of real-time monitoring system for aquaculture farming using IOT / Othman Hanafi Yusoff - Yusoff, Othman Hanafi (2017)
This project presents a real-time monitoring system for aquaculture that using Intel® Edison as a microcontroller to interface with the cloud storage. Sensors that have been implanted are the input which provides the microcontroller measurement from the fish pond. The aim of this project is to design and develop a system that monitors the rate of nutrition contains in the commercial freshwater fish pond. The project is divided into the following scopes; a) interface connection between Intel® Edison with IBM Cloud and b) develop a way for the end user to get the information that in the database. All controls are centralized using the Intel® Edison as a microcontroller and the data are obtained from the temperature, Dissolved Oxygen and pH sensor. Then the data is stored in the cloud storage and make the user accessible using their personal computer and mobile phone. The user can monitor the data at anywhere as long there is Internet connection on their mobile phone. This project is the new technology in the fish farms industry and will counter problem occurs nowadays.